A facile chemical synthesis of ZnO@multilayer graphene nanoparticles with fast charge separation and enhanced performance for application in solar energy conversion. (July 2016) - Shim, Jaeho; Kim, Jung Kyu; Lee, Kyu Seung; Lee, Chang-Lyoul; Ma, Ming; Choi, Won Kook; Hwang, Jun Yeon; Yang, Hee Yeon; Angadi, Basavaraj; Park, Jong Hyeok; Yu, Kyoungsik; Son, Dong Ick
Abstract: This work reports on the in-situ chemical synthesis and their properties of multilayer graphene (MLG) shells, made by unzipping single walled carbon nanotubes (SWCNTs), on the surface of Zinc oxide (ZnO) core nanoparticles (NPs). The stable oxygen bridge bonds between the ZnO core and the oxygen-related functional groups on the MLG shells facilitate the efficient photoinduced charge separation. This charge separation mechanism is confirmed experimentally using time-correlated single photon counting (TCSPC) measurements. The calculated average carrier lifetimes of the ZnO@MLG NPs are approximately 10 2 times faster than those for the bare ZnO NPs. The efficient electron transfer between the ZnO core and the MLG shell resulted in the significant improvement of the photocatalytic activity and the photoelectrochemical response. Simultaneously, the photocorrosion of ZnO was prevented by having the oxygen bridge bonds between the ZnO and MLG which suppressed the photo-generated holes oxidizing the surface oxygen atoms on ZnO, and in turn the holes are consumed by photocatalytic reaction. The 4.3 times enhanced photocurrent density at 0.2 V vs. Ag/AgCl (pH 6.9) and around 10 times higher rate constant value of photodegradation of rhodamine B were achieved by ZnO@MLG NPs in comparison with those of bare ZnO NPs. Graphical abstract: Highlights: A simple and facile technique for synthesis of ZnO@MLG NPs from SWCNTs. Strong bonds between a ZnO core and a multilayer graphene shells enhance charge separation properties and the long-term stability. The quenching ratio and FRET efficiency are significantly increased by more than 98%.